Autism spectrum disorder (ASD) symptom profiles of children with comorbid Down syndrome (DS) and ASD: A comparison with children with DS-only and ASD-only. (June 2019) - Godfrey, Mary; Hepburn, Susan; Fidler, Deborah J.; Tapera, Tinashe; Zhang, Fengqing; Rosenberg, Cordelia Robinson; Raitano Lee, Nancy
Highlights: Social-communication is weaker in children with autism than in Down syndrome and comorbid autism. Symptom profiles differ among autism, Down syndrome, and comorbid Down syndrome and autism. Verbal skills are strongly related to social-communication in Down syndrome and comorbid autism. Abstract: Background: Down syndrome (DS) is associated with increased rates of autism spectrum disorder (ASD), characterized by social−communicative impairments (SOC−COM) and repetitive behaviors and interests (RBI). However, little is known about the ASD symptom presentation in children with DS + ASD. Aims: The current study sought to describe parent-report of SOC−COM and RBI symptoms on the Autism Diagnostic Interview -Revised (ADI-R) in children with DS (n = 22), DS + ASD (n = 11), and ASD (n = 66). Method: SOC−COM and RBI scores from the ADI-R were compared across the groups whose autism status was ascertained using the Autism Diagnostic Observation Schedule. Results: Differences in SOC−COM and RBI symptom severity was observed. The general pattern of findings was ASD > DS+ASD > DS. Dissimilar ASD symptom profiles were observed across groups. In ASD, SOC−COM scores were higher than RBI scores; in DS + ASD, similar SOC−COM and RBI scores were observed. Lastly, SOC−COM impairments were highly related to verbal cognition in youth with DS + ASD but not in those with DS or ASD. Conclusions and Implications: These findings suggest that children with DS + ASD have a distinct profile of ASD symptoms that differs from peers with either disorder in isolation. Thus, care should be taken in evaluating and designing treatments for this group.